2007
DOI: 10.1002/dev.20218
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of vocal communication and discrimination between ewes and their lamb in the first two days after parturition

Abstract: In sheep, the mother-young relationship is characterized by an exclusive bond that relies on the rapid establishment of mutual recognition. However, the role of acoustic cues has been underestimated and neglected in this early discrimination. Therefore, the aim of the present study was (1) to characterize the vocal behavior of ewes and their lambs during the first 15 days postpartum and (2) to investigate the ability of newborn lambs and their mothers to discriminate each other from alien subjects within the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 47 publications
2
66
0
3
Order By: Relevance
“…Therefore, the higher vocal activity of nervous mothers is probably a general reflection of their nervous temperament rather than some specific difference of maternal behaviour with calm ewes. Furthermore, recent studies have shown that even high-pitched bleats are part of the normal repertoire of postparturient ewes and that vocal communication, both through low-and high-pitched bleats, is beneficial for the mother-young bond (Sè be et al, 2007 and2009) and that emission of high-pitched bleats tends to increase after parturition (Dwyer et al, 1998). Therefore, the difference in vocal activity encountered here between the two temperament lines of mothers is unlikely to contribute to the poorer lamb survival found in nervous ewes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the higher vocal activity of nervous mothers is probably a general reflection of their nervous temperament rather than some specific difference of maternal behaviour with calm ewes. Furthermore, recent studies have shown that even high-pitched bleats are part of the normal repertoire of postparturient ewes and that vocal communication, both through low-and high-pitched bleats, is beneficial for the mother-young bond (Sè be et al, 2007 and2009) and that emission of high-pitched bleats tends to increase after parturition (Dwyer et al, 1998). Therefore, the difference in vocal activity encountered here between the two temperament lines of mothers is unlikely to contribute to the poorer lamb survival found in nervous ewes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, olfaction is important in establishing maternal recognition by the lamb, and the development of the mother-young bond is reinforced by orogastro-intestinal stimulation ). However, while olfaction is the first proximal sense used (i) by the mother and infant to establish a bond, and (ii) by the male and female to identify social partners, visual (Kendrick et al 2001) and auditory (Sebe et al 2007, Sebe et al 2008 factors are also involved in the expression of social preferences.…”
Section: Social Behaviourmentioning
confidence: 99%
“…At very short range (,0.25 m in ewes, Alexander, 1978; ,1 m in goats, Poindron et al, 2003), recognition depends primarily on olfactory cues (Lé vy et al, 1996;Kendrick et al, 1997) and it controls the selective access of their own young to the udder (Lé vy et al, 2004). At greater distances recognition depends on visual and acoustic cues (Alexander and Shillito, 1977;Alexander, 1978;Poindron et al, 2003;Sè be et al, 2007). As these two systems are independent (Poindron et al, 2007a and2007c), they were both taken into account to assess maternal recognition in the present study.…”
Section: Introductionmentioning
confidence: 99%